Zero Fluoroscopy Arrhythmias Catheter Ablation: A Trend Toward More Frequent Practice in a High-Volume Center - Troisi, Federica; Guida, Pietro; Quadrini, Federico; Di Monaco, Antonio; Vitulano, Nicola; Caruso, Rosa; Orfino, Rocco; Cecere, Giacomo; Anselmino, Matteo; Grimaldi, Massimo (Frontiers in Cardiovascular Medicine, 2022)
Background Awareness of radiation exposure risks associated to interventional cardiology procedures is growing. The availability of new technologies in electrophysiology laboratories has reduced fluoroscopy usage during arrhythmias ablations. The aim of this study was to describe procedures with and without X-Rays and to assess feasibility, safety, and short-term efficacy of zero fluoroscopy intervention in a high-volume center oriented to keep exposure to ionizing radiation as low as reasonably achievable. Methods Cardiac catheter ablations performed in our hospital since January 2017 to June 2021. Results A total of 1,853 procedures were performed with 1,957 arrhythmias treated. Rate of fluoroless procedures was 15.4% (285 interventions) with an increasing trend from 8.5% in 2017 to 22.9% of first semester 2021. The most frequent arrhythmia treated was atrial fibrillation (646; 3.6% fluoroless) followed by atrioventricular nodal reentrant tachycardia (644; 16.9% fluoroless), atrial flutter (215; 8.8% fluoroless), ventricular tachycardia (178; 17.4% fluoroless), premature ventricular contraction (162; 48.1% fluoroless), and accessory pathways (112; 31.3% fluoroless). Although characteristics of patients and operative details were heterogeneous among treated arrhythmias, use of fluoroscopy did not influence procedure duration. Moreover, feasibility and efficacy were 100% in fluoroless ablations while the rate of major complications was very low and no different with or without fluoroscopy (0.45 vs. 0.35%). Conclusion Limiting the use of X-Rays is necessary, especially when the available technologies allow a zero-use approach. A lower radiation exposure may be reached, reducing fluoroscopy usage whenever possible during cardiac ablation procedures with high safety, full feasibility, and efficacy.